Pembubutan Aluminium 6061 dengan Fluida Potong Hibrida Berbasis Minyak Nabati Menggunakan Metode MQL - Mohammad Anshori; Agus Sulistiawan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study investigates the performance of hybrid cutting fluids derived from rubber seed oil and coconut oil in the turning of Aluminium 6061 using the Minimum Quantity Lubrication (MQL) technique. The research aims to evaluate the influence of cutting fluid flow rate and coconut oil concentration on surface roughness. Turning experiments were conducted at a spindle speed of 500 rpm, a feed rate of 0.011 mm/rev, and a depth of cut of 0.5 mm. The cutting fluid flow rates were set at 50, 100, and 150 ml/h, while the coconut oil content was varied at 5%, 10%, and 15%. Each experimental condition was repeated three times to ensure data reliability. The results show that increasing both the fluid flow rate and the coconut oil fraction consistently reduces surface roughness. The minimum surface roughness of 0.924 µm was obtained at a flow rate of 150 ml/h with 15% coconut oil. These findings indicate that hybrid vegetable-oil-based cutting fluids are a promising biodegradable alternative for sustainable, precision-turning applications.